Development of a structured observational method for the systematic assessment of school food-choice architecture. Issue 2 (3rd March 2016) - Ozturk, Orgul D.; McInnes, Melayne M.; Blake, Christine E.; Frongillo, Edward A.; Jones, Sonya J.
ABSTRACT: The objective of this study is to develop a structured observational method for the systematic assessment of the food-choice architecture that can be used to identify key points for behavioral economic intervention intended to improve the health quality of children's diets. We use an ethnographic approach with observations at twelve elementary schools to construct our survey instrument. Elements of the structured observational method include decision environment, salience, accessibility/convenience, defaults/verbal prompts, number of choices, serving ware/method/packaging, and social/physical eating environment. Our survey reveals important "nudgeable" components of the elementary school food-choice architecture, including precommitment and default options on the lunch line.